The Impact of Institutional Quality on Carbon Dioxide Emission : A Case Study in Asia - Pasific Countries - Budianto, Mahmud; Kusumawardani, Deni (International Journal of Economics Development Research (IJEDR), 2024)
Environmental issues occurring in the Asia Pacific region have become a highlight among state institutions. The recent increase in carbon dioxide emissions is considered a representation of environmental damage. The purpose of this study is to examine the effect of institutional quality on carbon dioxide emissions in 24 Asia Pacific countries. The interaction variables of GDP per capita and institutional quality, EKC hypothesis, urbanization and energy consumption are also used. The data were processed using STATA version 17 using the Generalize Moment of Method (GMM) estimation. The results of the study indicate that institutional quality, the interaction of GDP per capita and institutional quality have a significant negative effect on carbon dioxide emissions. GDP per capita has a significant negative effect on carbon dioxide emissions, but GDP per capita squared is significantly positive, meaning that the EKC hypothesis in the Asia Pacific case is contrary to the EKC Inverted U theory. Meanwhile, urbanization has a significant negative effect and energy consumption has a significant positive effect on carbon dioxide emissions. Finally, this study also suggests some valuable policy suggestions for governments/policymakers in general/specifically regarding developing countries to support their environmental sustainability.